"Antibureaucratism" as a Yugoslav Phenomenon: The View from Northwest Croatia. Issue 4 (July 2019) - Archer, Rory
Abstract: Most studies of the antibureaucratic revolution have focused on political elites and activists in Serbia, Montenegro, and the autonomous provinces of Vojvodina and Kosovo. Recent scholarship has focused on individual participants, often workers, and takes their agency seriously. Building upon such research, this article explores the antibureaucratic revolution as a particular manifestation of a larger sociocultural process, constitutive of long-term structural changes across the whole of Yugoslavia. An analysis of workplace documents and local newspapers in northwest Croatia demonstrates that antibureaucratic sentiment was not the prerogative of Serbian and Montenegrins but of Yugoslav citizens more generally. Yugoslavs were conditioned by the party-state to be critical of bureaucracy. Workers began to admonish the expansion of administrative positions, which they blamed for their falling living standards. Despite decentralizing and autarkic tendencies in political and economic life in late socialist Yugoslavia, working class discontents (and representations of it) remained remarkably similar across republican boundaries. In Rijeka and its environs, a shift does not occur until in mid-1988. Condemnations of nationalism become more urgent and a skepticism toward the mass protests occurring in Serbia is palpable from this point onward.